The eff ect of hydrogen content on the energy content that can be transferred through the natural gas transmission network - GalyasAnna Bella (Bányászati és Kohászati Lapok, 2024)
One of the most urgent problems today is taming the climate change. The most signifi cant sources of the problem are the release of energy use associated greenhouse gases of the atmosphere. There is also a growing demand at European level for renewable energy sources that can partially or fully replace traditional fossil fuels. Hydrogen promises to be suitable for this purpose. One of the biggest advantages of renewable hydrogen over current fossil fuels is that it produces water vapour when combusted, signifi cantly reducing CO2 emissions into the atmosphere. However, the energy content of hydrogen per unit volume is signifi cantly lower than for natural gas. This raises a signifi cant question of the extent to which the blending of hydrogen with natural gas modifi es the energy content that can be transferred through the pipeline. To quantify this, the KF conversion factor has been introduced, which shows the amount of transferable energy content reduction that occurs on a given pipeline section compared to pure methane content with constant pressure loss when hydrogen is already mixed into the main component of natural gas.